A Study of Heterogeneous Catalysis by Nanoparticle‐Embedded Paper‐Spray Ionization Mass Spectrometry. Issue 41 (16th September 2016) - Banerjee, Shibdas; Basheer, Chanbasha; Zare, Richard N.
Abstract: We have developed nanoparticle‐embedded paper‐spray mass spectrometry for studying three types of heterogeneously catalyzed reactions: 1) Palladium‐nanoparticle‐catalyzed Suzuki cross‐coupling reactions, 2) palladium‐ or silver‐nanoparticle‐catalyzed 4‐nitrophenol reduction, and 3) gold‐nanoparticle‐catalyzed glucose oxidation. These reactions were almost instantaneous on the nanocatalyst‐embedded paper, which subsequently transferred the transient intermediates and products to a mass spectrometer for their detection. This in situ method of capturing transient intermediates and products from heterogeneous catalysis is highly promising for investigating the mechanism of catalysis and rapidly screening catalytic activity under ambient conditions. Abstract : Reaction monitoring looks good on paper : Ambient‐condition paper‐spray ionization from nanoparticle‐doped paper allows the identification of reaction mechanisms and enables rapid screening of catalytic activity.